Earth Connections II Member Manual - Elise J. Cassie; Craig R. Miller; Joy Cantrell Jordan (EDIS, 2002)
This information was published November 1992 as 4-HESM 50, Florida Cooperative Extension Service. Reviewed June 2000. Revised on 10-09-2001. Reviewed June 2002.